KEPEMIMPINAN MULTIDIMENSI KEPALA MADRASAH DARI PERSPEKTIF GURU - Rahman, Bujang (Analisis: Jurnal Studi Keislaman, 2014)
THE MULTIDIMENSIONAL LEADERSHIP OF MADRASAH LEADER   IN TEACHER’S   PERSPECTIVE:   The  quality   of the  madrasa  leadership has  contributed  greatly  to  the  success of education  in the  school. As the  leader  of the  organization/ educational  institution, the main role  of the madrasah leader  is as a manager  and an administrator. As an instructional  leader, the  main  role   of the  madrasah  leader is as an educator  and a supervisor.  This  paper  aims  to  explain  how a madrasah  leader performs his/her role in the leadership of madrasah in the   four dimension of leaderships and its implications for the effectiveness of  education   in  madrasah.  A  total   of  120  teachers from  16 madrasah (MTs and MA) with varied backgrounds were involved in this study. With the Cronbach Alpha of the research instrument0.917, empirically the research revealed that madrasah leader role as an administrator dominated  over the roles as a manager and supervisor which were relatively  similar. Meanwhile, the role as an educator seemed to be very weak. This indicates that madrasah leaders need to enhance their role  as instructional  leaders as this has direct  impacts  on the establishment  of conducive academic atmosphere   at   madrasah.  Ideally,   to   achieve   the   optimized outcomes of education in madrasah, these four dimensions should be run in a balanced manner.